ANALISIS PRAKTIK PERATAAN LABA SERTA FAKTOR YANG MEMPENGARUHINYA PADA PERUSAHAAN INDUSTRI YANG TERDAFTAR DI BURSA EFEK INDONESIA (2005-2009) - Pieter Nainggolan; Adiwena Jaya Gunawan (Jurnal Akuntansi Bisnis, 2017)
This research was designed to examine factors that influence the practice of income smoothing of company size, company profitability, financial leverage, the net profit margin, and operating profit margin. The separation between companies that perform smoothing earnings and that do not perform by using Index Eckel against operating profit for the company's chemical industry and consumer goods registered in the Indonesian Stock Exchange. Sample research accounted for 36 companies with a sub sample of 180 financial statement data. Observations were made over five years,namely 2005,2006,2007,2008,2009. Factors not affecting income smoothing practices are summarized in the form of the null hypothesis. Statistical analysis consisted of: (1) univariate tests, to determine whether significant differences between the company and not leveler leveler, in this case using t-test if normally distributed data and Mann-Whitney test if data were not normally distributed, (2) multivariate test, using logistic regression to determine the factors that affect income smoothing. The result of calculation by Eckel Index shows that as many as 25 companies that make the practice of income smoothing. While the results of logistic regression analysis of four independent variables suspected to affect the practice of income smoothing turns out company size, company profitability, financial leverage, the net profit margin and operating profit margin has no effect on practice income smoothing.Key Word : Perataan Laba (income smoothing), manajemen laba (earnings management)